UPAYA MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SEDERHANA MENGGUNAKAN MODEL CONCEPT SENTENCE DENGANMEDIA GAMBAR PADA SISWA KELAS III SEKOLAH DASAR - Barina, Yulia; Silalahi, Mery (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2018)
This study aims to improve the learning outcomes of third grade students of SD Negeri 066652 Bakti Luhur in writing simple material through the Concept Sentence model with Picture Media. This research is Kemmis and Mc Class Action Research (CAR). Taggart The research subjects were class III students, totaling 20 students. Data collection techniques to see the implementation of learning Concept Sentence with Media Images using observation, while looking at student learning outcomes using tests, research instruments using test sheets and observation sheets. Data analysis techniques used descriptive quantitative and qualitative descriptive. The results showed that the application of the Concept Sentence learning model with Media Images in Indonesian Language learning could improve student learning outcomes in the material written in simple essays of class III SD Negeri No 066652 Bakti Luhur. This is evidenced by the increase in learning outcomes of class III students from cycle I to cycle II. Student learning outcomes in cycle I with an average of 62 and cycle II 83. The level of completeness in the first cycle is 40% and in the second cycle becomes 80%.